Tax Compliance Behavior of Generation Y and Z: A Study Based on the Theory of Planned Behavior - Kusuma, Made Cahyadi Wiranata; Ratnadi, Ni Made Dwi; Hasibuan, Henny Triyana (Amkop Management Accounting Review (AMAR), 2025)
Low tax compliance among individual taxpayers, particularly Generations Y and Z, poses a challenge to optimizing national revenue. This study aims to examine the influence of attitude toward behavior, subjective norms, and perceived behavioral control on behavioral intention, as well as the impact of intention on tax compliance. It also explores intergenerational differences and the mediating role of intention in the relationship between attitude and tax compliance. Employing the Theory of Planned Behavior, data were collected via questionnaires from 300 respondents in Denpasar City and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that attitude significantly influences intention among Generation Z, while subjective norms are the dominant factor among Generation Y. Behavioral intention significantly mediates the effect of attitude on tax compliance for Generation Z. The study recommends generationally tailored tax education strategies to enhance sustainable tax compliance.